EARLY REHABILITATION AFTER STROKE IN THE NEUROSURGICAL CLINIC OF SAMARKAND - Kilichev Farrukh Akhmadovich (Research Focus International Scientific Journal, 2025)
Stroke remains one of the leading causes of disability and mortality worldwide. The experience of the Neurosurgical Clinic of Samarkand demonstrates that early and structured neurorehabilitation significantly improves functional recovery and quality of life in stroke patients. The study highlights the importance of early verticalization, postural therapy, ontogenetic kinesiotherapy, and comprehensive pharmacological support aimed at restoring cerebral perfusion, enhancing neuroplasticity, and preventing complications. Rehabilitation programs focus on early activation, self-care training, dysphagia management, and prevention of painful shoulder syndrome and arthropathies. The integration of physiotherapy, ergotherapy, and neuroprotective pharmacotherapy provides optimal conditions for neuronal repair and social reintegration. Early neurorehabilitation, initiated within the first hours and days after stroke, should be considered a fundamental component of modern stroke care.